Improving Spelling Learning In Primary School Age Through Songs - Budiman, Muhammad Arief; Widyaningrum, Ari; Azizah, Mira (Universitas Pendidikan Ganesha, 2020)
English needs to be taught from an early age, at the basic education level. Teachers in elementary schools are required to provide an interesting and easy-to-understand English learning experience for students. However, the problem is that not all teachers in elementary schools have that ability. Only a few teachers can create learning English creatively. One of them is a teacher at Kramat Elementary School, Kudus Regency. The teacher at the elementary school taught English on spelling learning material through the media of songs. This research aimed to examine in depth the use of song media to increase elementary school-aged children's spelling learning. This research is qualitative, aiming to deepen the study of spelling learning for elementary school-aged children and their solutions to globally improve the quality of primary school education. This research's object is the teachers and students of SDN Kramat, Kudus Regency with the data collecting technique of observation, interviews, and documentation. The data obtained is then analyzed using Miles & Huberman (1992) analysis technique, including activities of reduction, data presentation, and conclusion/verification. The results showed that the use of songs in learning English, especially spelling learning in elementary schools, was able to have a positive impact on both teachers and students. The impact for teachers is to provide awareness that creativity is something important for them to improve professionalism. For students, the song is an effective medium to increase learning motivation and understand the material. The conclusion in this study is that the use of song media in spelling learning impacts teacher creativity and increases elementary school students' English learning outcomes